Bioremediation of hydrocarbon contaminated- soils using locally isolated P.Aeruginosa with organic and inorganic fertilizers / Siti Zulaikha Shaikuthali - Shaikuthali, Siti Zulaikha (2019)
Oil contaminated wastewater is the most concerned pollution because it is harmful to the flora and fauna. Oil spills is the major source for oily wastewater. This oil spills will contaminate the marine sediments, soils and water. Biodegradation method is the most used method because it using microorganisms to degrade the hydrocarbon into less contaminated forms. This is because biological method is environmental friendly and cost effective. The microorganisms will degrade the contaminants in soil by using the hydrocarbon as the energy source. The discharge of oil into the ocean which have low concentrations of inorganic nutrients regularly deliver a lot of carbon/nitrogen or carbon/phosphorus ratios, or both, which are bad for bacterial development. Besides that, the lack of nutrients for microorganisms also can affect the biodegradation of hydrocarbon. Thus, this research aim to study the effect of organic and inorganic fertilizer addition to the growth rate of locally isolated Pseudomonas Aeruginosa. Next, is to investigate the effectiveness of inorganic nutrient (NPK and urea) and organic nutrient (SW and ESP) to stimulate the natural bioremediation process of hydrocarbon contaminated soils. The soil samples that taken from Port Dickson beach will be isolated and identified by using cetrimide agar. Pseudomonas Aeruginosa that was isolated from soil samples taken from Port Dickson beach were used in degradation of different hydrocarbon (kerosene and diesel) polluted soils added with inorganic (NPK and Urea) and organic (SW and ESP) fertilizers and in some of their mixture. The incubation period ranged from 0-18 days. Throughout the experiment, the TPH and bacterial growth was determined. Results showed that bacterial population is increasing throughout the experiment until day 15 due to the presence of essential nutrients. Bacterial counts is increasing as the microorganisms consumed hydrocarbon for carbon and energy, residual hydrocarbon decreased was stimulated by the fertilizer and percentage degradation increased. Pseudomonas Aeruginosa degraded kerosene and diesel better in the existence of NPK and urea fertilizers. More than 90% of the hydrocarbons were degraded with each incubation period. Bacterial population after 15th day it begins to drop because of the secretion of toxic secondary metabolites that may cause harm to microbes itself. Furthermore, Pseudomonas Aeruginosa degrade kerosene oil better than the diesel oil.